Association of 25-hydroxyvitamin D, Cyclooxygenase-2 and Prostaglandin E2 Serum Levels in Breast Cancer Patients - Theresia Ilyan; Dwi Retnoningrum; Meita Hendrianingtyas; Dian Widyaningrum; Banundari Rachmawati (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Serum levels of 25-hydroxyvitamin D (25(OH)D), prostaglandin E2 (PGE2), and cyclooxygenase 2 (COX2) expression differ between breast cancer stages. Since, previous studies showed mixed results, in this study, we aimed to analyze vitamin D levels related to breast cancer stages and serum levels of COX2 and PGE2 in Indonesia.METHODS: This was a cross sectional study involving 75 breast cancer patients. Subjects were divided into 3 groups, namely operable early stage (K1), locally advanced stage (K2), and advanced stage (K3). Venous blood samples were taken from each subject, then were analyzed for the 25(OH)D, COX2, and PGE2 serum levels by enzyme-linked immunosorbent assay (ELISA) method.RESULTS: There were significant differences in 25(OH)D among groups (p=0.012); between K1 and K2 (p=0.009) and between K1 and K3 (p=0.023). However, there was no significant difference in serum COX2 level (p=0.328). There were significant differences of PGE2 among groups (p=0.002); between K1 and K2 (p=0.036) and between K1 and K3 (p=0.001). Correlation test showed that there were differences between 25(OH)D serum levels and PGE2 serum level (r=0.306, p=0.008) and also between 25(OH)D serum level and breast cancer stage (r=-0.229; p=0.048).CONCLUSION: There were differences in serum Vitamin D and PGE2 levels at various stages of breast cancer. Serum 25(OH)D levels had weak correlation with breast cancer stage and PGE2 serum level. Serum vitamin D level in advanced breast cancer were lower than early stage breast cancer and indicate a poor prognosis.KEYWORDS: breast cancer, 25-hydroxyvitamin D, cyclooxygenase 2, prostaglandin E2